2016
DOI: 10.1111/jphp.12497
|View full text |Cite
|
Sign up to set email alerts
|

Prominent efficiency in skin delivery of resveratrol by novel sucrose oleate microemulsion

Abstract: MESO-E would be a promising vehicle for the efficient skin delivery of resveratrol, especially when applied at a low concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Labrasol ® (PEG-8 Caprylic/Capric Glycerides -CAS# 85536-07-8) and Transcutol ® (Ethoxydiglycol -CAS# 111-90-0) were gifts from Gattefossé (Saint-Priest, France). Orthophosphoric acid, hematoxylin, eosin and ethanol were purchased from Thermo Fisher Scientific A range of approaches have been investigated to improve the topical delivery of RSV, including micro/nanoemulsions [14], niosomes [15], ethosomes [16], nanosponges [17], microparticles [18], and nanoparticles [19]. Nano/microemulsions provide particular advantages for a topical product formulation because they are transparent optically isotropic and kinetically stable colloids [20].…”
Section: Methodsmentioning
confidence: 99%
“…Labrasol ® (PEG-8 Caprylic/Capric Glycerides -CAS# 85536-07-8) and Transcutol ® (Ethoxydiglycol -CAS# 111-90-0) were gifts from Gattefossé (Saint-Priest, France). Orthophosphoric acid, hematoxylin, eosin and ethanol were purchased from Thermo Fisher Scientific A range of approaches have been investigated to improve the topical delivery of RSV, including micro/nanoemulsions [14], niosomes [15], ethosomes [16], nanosponges [17], microparticles [18], and nanoparticles [19]. Nano/microemulsions provide particular advantages for a topical product formulation because they are transparent optically isotropic and kinetically stable colloids [20].…”
Section: Methodsmentioning
confidence: 99%
“…RESV permeated the different layers of the skin in an average concentration of 11.25 ± 6.56 µg/cm 2 136 . When applied in the concentration range of 5-55 mM, the amount of skin incorporation of RESV increased with the applied concentration up to 30 mM, whereas skin incorporation efficiency was inversely proportional to the applied concentration and when applied with 10% ethanol, in the epidermis the concentration was 0.02 µM 137 . Hence, RESV must be used at relatively high concentrations (e.g.…”
Section: Resveratrol and Skinmentioning
confidence: 95%
“…A recent work by Alonso et al has assessed in both in vitro and in vivo the permeation of topical application of resveratrol, showing that the topically applied resveratrol penetrates into the skin in a gradient fashion and that resveratrol after its penetration was able to maintain its antioxidant efficiency [40]. Nevertheless, it was demonstrated that resveratrol must be used at relatively high concentration for topical in vivo application in order for it to be effective [41].…”
Section: Discussionmentioning
confidence: 99%